2015
DOI: 10.3389/fphar.2015.00272
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocins as Potential Anticancer Agents

Abstract: Cancer remains one of the leading causes of deaths worldwide, despite advances in its treatment and detection. The conventional chemotherapeutic agents used for the treatment of cancer have non-specific toxicity toward normal body cells that cause various side effects. Secondly, cancer cells are known to develop chemotherapy resistance in due course of treatment. Thus, the demand for novel anti-cancer agents is increasing day by day. Some of the experimental studies have reported the therapeutic potential of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
179
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(206 citation statements)
references
References 89 publications
(101 reference statements)
1
179
0
6
Order By: Relevance
“…In this trend, the number of reports concerning bacteriocins as antiprotozoal agents (20)(21)(22)(23) is surprisingly lower than that of reports aiming at other eukaryotic targets such as fungi (24)(25)(26) or even tumoral cells (27)(28)(29).…”
mentioning
confidence: 77%
“…In this trend, the number of reports concerning bacteriocins as antiprotozoal agents (20)(21)(22)(23) is surprisingly lower than that of reports aiming at other eukaryotic targets such as fungi (24)(25)(26) or even tumoral cells (27)(28)(29).…”
mentioning
confidence: 77%
“…Recent studies have indicated the activity of bacteriocins against some tumor cell lines in vitro [22]. Colicin A and E1 produced by E. coli demonstrated growth inhibition of human fibroblast, bone, breast and colon cancer cells amongst other cell lines in vitro [46]. Colicin D and E3 was shown to induce a dose dependent inhibition of murine leukemia cells at 0.4, 0.8, 1.6 and 3.2 mg/mL in vitro [36].…”
Section: Anti-cancer Activitymentioning
confidence: 99%
“…Bacteriocins with anticancer activity appear to be cationic, amphiphilic and membrane active with cytoxicity due to necrotic cell membrane lysis induced by increased presence of negatively charged molecules on the membrane surface [7]. Additionally, cancer cells have higher membrane fluidity compared to normal cells allowing for membrane destabilization [46]. Moreover, other bacteriocins are known to affect angiogenesis, subsequent cancer progression, disrupt the integrity of mitochondrial membrane and induce apoptosis and cell cycle arrest in cancer cells [49].…”
Section: Anti-cancer Activitymentioning
confidence: 99%
“…There have been some suggestions that bacteriocins can be employed as anticancer agents, either through their impact on cancerous cells or through the inhibition of bacteria associated with the initiation of disease 60 . One such study focused on the impact of nisin on head and neck squamous cell carcinoma (HNSCC) cell apoptosis and cell proliferation in vitro and in vivo in murine oral cancer 61 .…”
Section: Novel Health Targets For Bacteriocinsmentioning
confidence: 99%